Analisis Faktor Konfirmatori Terhadap Skala Cyberloafing Mahasiswa - Megawati, Hermeilia; Rustyawati, Reny; Suryaratri, Ratna Dyah; Kusumawardhani, Sri Juwita (Journal of Research and Measurement in Psychology: JPPP, 2023)
The implementation of online distance learning creates a new deviant behaviour in higher education students. There are symptoms of student behaviour who negligent in using the internet for purposes that are not related to learning which is known as cyberloafing. Considering the rapid development of technology, the measurement of student cyberloafing behaviour needs to be developed continuously. Thus, this study aims to develop previous scales related to student cyberloafing to stay up to date. Based on literature review that discusses the measurement of student cyberloafing, a 20-item scale form created. The data were collected from 506 undergraduate students at a large university in Jakarta who have online distance learning experiences. Data were analysed using Confirmatory Factor Analysis (CFA) with the JASP program. The results of this study indicate that the student cyberloafing scale model is in accordance with the theory where three dimensions are indicated, namely social purpose cyberloafing, academic cyberloafing, dan gaming purpose cyberloafing. The scale has a good fit model based on CFI, TLI, RMSEA, SRMR and GFI. Keywords: confirmatory factor analysis; cyberloafing; student cyberloafing; student cyberloafing scale